Pacemaker-Mediated Programmable Hypertension Control Therapy - Neuzil, Petr; Merkely, Béla; Erglis, Andrejs; Marinskis, Germanas; de Groot, Joris R; Schmidinger, Herwig; Rodriguez Venegas, Manuel; Voskuil, Michiel; Sturmberger, Thomas; Petru, Jan; Jongejan, Niels; Aichinger, Josef; et al. (Journal of the American Heart Association, 2017)
BACKGROUND: Many patients requiring a pacemaker have persistent hypertension with systolic blood pressures above recommended levels. We evaluated a pacemaker-based Programmable Hypertension Control (PHC) therapy that uses a sequence of variably timed shorter and longer atrioventricular intervals. METHODS AND RESULTS: Patients indicated for dual-chamber pacing with office systolic blood pressure (oSBP) >150 mm Hg despite stable medical therapy were implanted with a ModeratoTM pulse generator that delivers PHC therapy. Patients were followed for 1 month (Run-In period) with conventional pacing; those with persistent oSBP >140 mm Hg were included in the study and had PHC therapy activated. The co-primary efficacy end points were changes in 24-hour ambulatory systolic blood pressure and oSBP between baseline and 3 months. Safety was assessed by tracking adverse events. Thirty-five patients met the initial inclusion criteria and underwent Moderato implantation. At 1 month, oSBP was <140 mm Hg in 7 patients who were excluded. PHC was activated in the remaining 27 patients with baseline office blood pressure 166±11/80±10 mm Hg despite an average of 3.2 antihypertensive medications. During the Run-In period, oSBP and 24-hour ambulatory systolic blood pressure decreased by 8±13 and 5±12 mm Hg (P<0.002), respectively. Compared with pre-PHC activation measurements, oSBP decreased by another 16±15 mm Hg and 24-hour ambulatory systolic blood pressure decreased by an additional 10±13 mm Hg (both P<0.01) at 3 months. No device-related serious adverse effects were noted. CONCLUSIONS: In pacemaker patients with persistent hypertension despite medical therapy, oSBP and 24-hour ambulatory systolic blood pressure are decreased by PHC therapy. Initial indications are that this therapy is a safe and promising therapy for such patients. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02282033.
Keywords: Follow-Up Studies; prospektivní studie; Heart Rate; Humans; lidé; krevní tlak; následné studie; srdeční frekvence; Treatment Outcome; kardiostimulátor; Hypertension; ambulantní monitorování krevního tlaku; Female; Male; Prospective Studies; hypertenze; výsledek terapie; mužské pohlaví; Aged; ženské pohlaví; Blood Pressure Monitoring, Ambulatory; Pacemaker, Artificial; Blood Pressure; senioři